(3EOGQI GdeDSSGJ GdeGdjI hGdeUQajI (B/s - (3GdYHjOj, QGFO YHO GdNGdb YHO Gddgs; (3GdeTgOGfj, NGdO CMeO aQMGfs ((3YeGf(B: s (3OGQ GdGjGe(B, s, 2015)
(3jVe Cge GdJYGQja hGdeaGgje GdeGdjI, GdDSSGJ GdeGdjI hGdfbOjI, GdQjGVjGJ GdeGdjI, EOGQI GdejRGfjI aj GdDSSGJ GdeGdjI h GdeUQajI , GdeUGQa hCfhGYgG hhXGFagG hCgejJgG , GdeUGQa GdGSdGejI (B-(3GdfbhO hGdeUGQa, EOGQI GdNWQ aj GdDSSGJ GdeGdjI hGdeUQajI hGdJCejf, EOGQI GdeMGaX GdGSJKeGQjI, GdDSSGJ GdeGdjI GdOhdjI, GdebheGJ GdGSGSjI GbQGQGdGSJKeGQ, GdeDSSGJ GdeGdjI hGdeUQajI aj GdYQGb, GdHjFIGdeGdjI cGdGShGb GdeGdjIhGdfbOjI, GdNOeGJ GdeGdjI hJWhQgG aj GdYbhOGdGNjQIs
(3GdeQGLY U(B.192s
Keywords: (3EOGQI(B- (3GdeDSSGJ GdeGdjIs; (3GdEOGQI GdeGdjIs; (3GdHfhc(B- (3EOGQIs